Systematic analysis of photo/sko-regulated germination and post-germination development of shallow photodormant seeds in Nicotiana tabacum L. - Liu, Qiyuan; Li, Zhenhua; Zhang, Min; Dong, Shuai; Yang, Pingping; Zhang, Jie; Loades, Eddison (Frontiers in Plant Science, 2023)
Light is a major environmental factor in regulating germination and post-germination development of shallow photodormant seeds in Nicotiana tabacum L. (tobacco). However, its molecular mechanism remains largely unclear. In this study, we compared the phenotypes of the seeds germinated under light and dark, and systematically investigated their regulatory networks by integrating transcriptomic and proteomic data. Under light, the germination increased ~25%, the length of the hypocotyl shortened ~3 cm, and the apical hook disappeared. 8, 161, 341 differentially expressed genes (DEGs) and 128, 183, 100 differentially expressed proteins (DEPs) regulated by light were identified on 2 days after imbibition (DAI 2), DAI 4 and DAI 6, respectively. 0, 19 and 1 co-up-regulated and 1, 30 and 64 co-down-regulated DEGs (DEP) were observed at that time, respectively. Of these co-up- and co-down-regulated DEGs (DEPs), Oleosin 18.5 kDa (OLEO1), Glyceraldehyde-3-phosphate dehydrogenase (GAPA1), Oxygen-evolving enhancer protein 1-1 and anchloroplastic (PSBO1) were the hub genes (proteins) on DAI 4, while OLEO1 was the hub of DAI 6. These results systematically revealed the molecular networks regulated by light during germination and post-germination development of shallow photodormant tobacco seeds.